Comparison of the color stability and surface roughness of 3-unit provisional fixed partial dentures fabricated by milling, conventional and different 3D printing fabrication techniques. (April 2023) - Ellakany, Passent; Fouda, Shaimaa M.; AlGhamdi, Maram A.; Aly, Nourhan M.
Abstract: Objectives: To compare the color stability and surface roughness of 3-unit provisional fixed partial dentures (FPDs) fabricated by milling, conventional, and different 3D printing fabrication techniques. Methods: A total sample of 160, 3-unit FPDs were subdivided into four groups; subtractive milled resin (SM), two 3D printed resins (Stereolithography; SLA and Digital Light Processing; DLP) and conventional self-cured polymethyl methacrylate resin (CM). Surface roughness (Ra) was assessed twice; at baseline (Ra1) and after artificial tooth brushing (Ra2). Color of the samples was measured after immersion in four different solutions (cola, coffee, black tea and distilled water) at three time intervals (1, 7 and 30 days). Comparisons of the Ra and the color change (∆E00 ) were done using one-way ANOVA followed by multiple pairwise comparisons using Bonferroni adjusted significance level. Comparisons of the Ra at two stages (Ra1 and Ra2) were done using paired t -test. Univariate linear regression was performed followed by multivariable regression to assess the association between ∆E00 and different factors (materials, solution, and time). Significance was set at P value <0.05. Results: The highest change in Ra following artificial tooth brushing was reported in the CM group, while the lowest change was reported in the SM group, with a significant difference between both groups ( P <0.001). SM group had significantly lower ∆E00 than the CM group followed by 3D printed SLA and DLP groups ( P <0.001). Storage in coffee for 30 days showed the highest ∆E00 values ( P <0.001). Conclusions: SM resin showed the least surface roughness and color change followed by 3D printed SLA resin. The difference in printing technology affected the tested properties with improved readings of 3D printed SLA resin. Clinical significance: Milled provisional FPDs showed higher surface smoothness and color stability than those fabricated by SLA printing technology, but with no significant difference between both groups. Therefore, SLA printed resins can be an adequate substitute to milled resins in the fabrication of provisional FPDs to overcome the high expenses of milled provisional FPDs.